Eating disorders symptoms and excessive internet use in adolescents: the role of internalising and externalising problems - Nika Šablatúrová (BMC, 2021)
Plain English summary The study found that, in adolescents, eating disorders symptoms are associated with excessive internet use even when controlled for their shared psychological factors. Self-control issues were associated with both the eating disorder symptoms and excessive internet use, while emotional issues were only associated with the eating disorder symptoms. The strength of the relationship was similar for boys and girls, even though the prevalence of eating disorders symptoms was double in girls.